1991
DOI: 10.1002/cne.903060410
|View full text |Cite
|
Sign up to set email alerts
|

A collagen‐based nerve guide conduit for peripheral nerve repair: An electrophysiological study of nerve regeneration in rodents and nonhuman primates

Abstract: When a peripheral nerve is severed and left untreated, the most likely result is the formation of an endbulb neuroma; this tangled mass of disorganized nerve fibers blocks functional recovery following nerve injury. Although there are several different approaches for promoting nerve repair, which have been greatly refined over recent years, the clinical results of peripheral nerve repair remain very disappointing. In this paper we compare the results of a collagen nerve guide conduit to the more standard clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
186
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(192 citation statements)
references
References 39 publications
1
186
1
4
Order By: Relevance
“…Axonal outgrowth, proceeding from the proximal stump through the substrate, is conditioned by the preceding events. The long-term functional recovery of nerve gaps in rodent and primate models using the collagen-based conduit are similar to primary anastomosis and autograft procedures (Archibald et al, 1991).…”
mentioning
confidence: 81%
“…Axonal outgrowth, proceeding from the proximal stump through the substrate, is conditioned by the preceding events. The long-term functional recovery of nerve gaps in rodent and primate models using the collagen-based conduit are similar to primary anastomosis and autograft procedures (Archibald et al, 1991).…”
mentioning
confidence: 81%
“…Yet, also SNI in primates has been used for pre-clinical testing of nerve scaffolds (Archibald et al, 1991) due to its closer similarities with human patients.…”
Section: Considerations About Selection Of the Animal Speciesmentioning
confidence: 99%
“…Artificial nerve conduit to bridge the gap between severed nerve stumps is widely accepted as a useful alternative that provides structural support and a favorable microenvironment for axonal regeneration [18]. The great advantage of collagen is very resorbable, and Archibald et al [19,20] described excellent regeneration following median nerve repair in monkeys as by. Its structure also offers biochemical support for nerve regeneration, as it has been showed that collagen is one of extra-cellular matrix (ESM) factors that has been shown to play a significant role in the process of nerve regeneration [6].…”
Section: Discussionmentioning
confidence: 99%